1953
DOI: 10.1111/j.1939-0025.1953.tb00066.x
|View full text |Cite
|
Sign up to set email alerts
|

An application of group therapy to the intake process.

Abstract: conscientious intake worker at an agency to which people T come, THE or are brought for help, it must often seem that there is a special demon who arranges matters so that 1) the people his agency is best prepared to serve rarely seem to arrive a t his office; 2) those who require facilities the agency feels unable to extend do appear with annoying frequency; and 3) a number of individuals who seem to be in greatest need of the agency's assistance and might derive benefit from it cannot be helped because they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1962
1962
1984
1984

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Most of what we have included in our program has been tried separately by others. Harris Peck (3) has applied group therapy to the intake process. Whitaker (4) has used multiple therapists as a part of brief therapy and found that resolution of countertransference problems is facilitated.…”
Section: Development Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of what we have included in our program has been tried separately by others. Harris Peck (3) has applied group therapy to the intake process. Whitaker (4) has used multiple therapists as a part of brief therapy and found that resolution of countertransference problems is facilitated.…”
Section: Development Of the Methodsmentioning
confidence: 99%
“…The present project has committed itself from the outset to the interactional viewpoint in its treatment of such family situations. 3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Four-week screening groups were also tried, but were shortened to two-weeks because many adolescents found termination painful after having established close relationships in the group over a four-week period. Peck (1953) found that intake groups of adolescent delinquents served to provide individual data as well as an opportunity to clarify what the adolescent thought the clinic could do. He reported that adolescents in intake groups became more realistic and better able to openly express their concerns and feelings.…”
Section: Orientation To Therapymentioning
confidence: 99%
“…For example, Bitterman (1958) reports using a program of telephone evaluations to judge applicants' tolerance for waiting, and scheduling first appointments appropriately. Taboroff, Brown, Kormer, Reiser, Talmadge, Goates, and Stein (1956); Stone, Parloff, and Frank (1954);and Peck (1953) report doing Intake diagnosis in short-term groups. Taboroff found that diagnostic ratings derived from observations of behavior in groups were similar to those accomplished by psychiatric interviews and psychological tests.…”
mentioning
confidence: 99%